Pengaruh Budaya Organisasi dan Komitmen Organisasi terhadap Working Engagement PT Bank Mandiri - Hairul, Hairul; Panggabean, Hana R.G (Universitas Muhammadiyah Metro, 2020)
Working Engagement is defined as high emotional engagement towards one’s occupation. An individual attaches themselves to their work role, actively participates in it, and places importance on their performance at work (Kaswan, 2017). This research aims to understand the influence of organizational culture and commitment on working engagement PT Bank Mandiri. This study was conducted on 83 individual employees at PT Bank Mandiri (Persero) Tbk. with a minimum of one year of the working period. The sampling technique was obtained by non-probability sampling, namely convenience sampling / accidental sampling. The data analysis method used is multiple linear regression. The result of this study indicates that Organizational Culture and Organizational Commitment do affect Working Engagement, with a predictive power of 35.8% and 31.7%, respectively. For further research, it is advisable to conduct a similar study on a larger population and combine quantitative and qualitative research methods. Suggestions for companies are to adjust programs and work environments that need to be more casual, such as changes in the workspace that is no longer cubicle, flexible working hours, and open communication between supervisors and subordinates.